Exocrine Glands : Proceedings of a Satellite Symposium of the XXIV International Congress of Physiological Sciences - Botelho, Stella Y.; Brooks, Frank P.; Shelley, Walter B. (University of Pennsylvania Press, 1969)
This volume collects an impressive amount of information about many of the challenging problems pertaining to the exocrine glands, discussed at this Satellite Symposium held at the University of Pennsylvania. This Symposium was one of the 18 highly specialized conferences, the detailed information and probing of which complemented the broader aims of the XXIV International Congress of Physiological Sciences held August 1968 in Washington, D.C. This Symposium attracted eminent physiologists from various countries throughout the world with eight of the seventeen formal papers being delivered by physiologists from abroad. Published with the papers are 122 illustrations, 103 of which have never before been printed; 42 tables, 38 of which have never before been published; and the complete discussion of all papers by 39 investigators.